DEVELOPMENT OF POWTOON-BASED LEARNING MEDIA ON CAPITAL MARKET MATERIAL FOR GRADE X OF STATE HIGH SCHOOL 1 ALALAK - Umi Hani; Mahmudah Hasanah; Baseran Nor; Alfi Fadhilah Hakim Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to develop a capital market material media product using the powtoon web application. This study measures the validity and practicality of the media. The method in this study is Research and Development (R&D) and uses the 4D model. The procedures in the development include (1) define, (2) design, (3) development, and (4) dissemination. The results of the research conducted show the development process of learning media using powtoon starting from a) initial analysis, students, assignments, concepts, and analysis of learning objectives b) selection of media, selection of formats, and design c) validation by experts and product trials. d) dissemination. The validation of material experts received a rating of 95.08% very valid. While expert validation for media with an assessment of 80% valid criteria. As for the product trial in the operational field for the results of student responses to the powtoon learning media. The assessment of the product trial in the operational field with a percentage of 87.30% is in the very practical category.